Information security risk assessment using situational awareness frameworks and application tools - Chandra, Nungky Awang; Ramli, Kalamullah; Ratna, Anak Agung Putri; Gunawan, Teddy Surya (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This paper describes the development of situational awareness models and applications to assess cybersecurity risks based on Annex ISO 27001:2013. The risk assessment method used is the direct testing method, namely audit, exercise and penetration testing. The risk assessment of this study is classified into three levels, namely high, medium and low. A high-risk value is an unacceptable risk value. Meanwhile, low and medium risk values can be categorized as acceptable risk values. The results of a network security case study with security performance index indicators based on the percentage of compliance with ISO 27001:2013 annex controls and the value of the risk level of the findings of the three test methods showed that testing with the audit method was 38.29% with a moderate and high-risk level. While the test results with the tabletop exercise method are 75% with low and moderate risk levels. On the other hand, the results with the penetration test method are 16.66%, with moderate and high-risk levels. Test results with unacceptable risk values or high-risk corrective actions are taken through an application. Finally, corrective actions have been verified to prove there is an increase in cyber resilience and security.